388 Preliminary results from KEYNOTE-A36, a study of GB1275, a first-in-class oral CD11b modulator, alone and with pembrolizumab or chemotherapy in specified advanced solid tumors. (9th November 2020) - Bendell, Johanna; Messersmith, Wells; Rasco, Drew; Wang-Gillam, Andrea; Park, Wungki; Zhou, Lei; Carter, Laura; Bruey, Jean-Marie; Li, Jack; Ferguson, Beatrice; Dupont, Jakob; Chaney, Marya; et al.
Abstract : Background: GB1275 is a first-in-class CD11b modulator that reduced myeloid-derived suppressor cells (MDSCs) and tumor associated macrophages (TAMs), repolarized M2 immunosuppressive TAMs to an M1 phenotype, and increased tumor infiltration of activated CD8+ T cells in preclinical models. Preclinical anti-tumor activity was observed with single-agent therapy and in combination with chemotherapy or immuno-oncology therapies. 1 We report results from the dose escalation portion of an ongoing, first-in-human study of GB1275 monotherapy and combined with pembrolizumab in patients with specific advanced solid tumors. (NCT04060342 ) Methods: This study comprises phase 1 dose escalation followed by phase 2 expansion in specific tumor types. In phase 1, cohorts of 3 to 6 patients with histologically confirmed, locally advanced/metastatic pancreatic, esophageal, gastric, MSS colorectal, metastatic castrate-resistant prostate cancer, or triple negative breast cancer are sequentially assigned to one of the ascending dose levels of GB1275 orally twice daily (BID) in 1 of 3 regimens: A (GB1275 monotherapy); B (GB1275 + pembrolizumab) commenced after completion of two cohorts of A; and C (GB1275 + nab-paclitaxel + gemcitabine) will be initiated after A. Patients in Regimens A and B had previously exhausted standard of care treatment options. Dose escalation was based on safety, including dose-limiting toxicity (DLT). Serial blood samples were collected for pharmacokinetic (PK) and biomarker analyses; tumor tissue was also collected for biomarker analysis. Results: As of July 28, 2020, 36 patients were treated, 23 in Regimen A (GB1275 100 mg to 1200 mg BID) and 13 in Regimen B (GB1275 100 mg to 800 mg BID + pembrolizumab). No DLTs or adverse events requiring steroid treatment were reported. GB1275-related adverse events were reported in 19 (52.8%) patients; most were Grade 1 and most frequent events (≥10%) were dysesthesia (13.9%) and photosensitivity reaction (11.1%). Stable disease was reported in 4 (17%) patients in Regimen A and 6 (46%) in Regimen B with a median (range) exposure of 84 days (35–172). A dose-dependent increase in GB1275 exposure was observed. An increase in tumor infiltrating lymphocyte (TIL) counts was noted in both Regimens A and B. Other biomarker analyses in serial blood and tumor tissue are ongoing. Conclusions: Dose escalation of GB1275, up to 1200 mg and 800 mg BID in Regimens A and B, respectively, demonstrated tolerability as monotherapy and combined with pembrolizumab. The maximum tolerated dose has not been reached. Preliminary observation of an increase in TILs after treatment is encouraging. Ethics Approval: This ongoing study is being conducted in accordance with the Declaration of Helsinki and Council for International Organizations of Medical Sciences (CIOMS) International Ethical Guidelines. The study was approved by the Ethics Boards of the University of Colorado Hospital, Washington University School of Medicine - Siteman Cancer Center, Memorial Sloan Kettering Cancer Center, The Sarah Cannon Research Institute/Tennessee Oncology, South Texas Accelerated Research Therapeutics, and The Royal Marsden NHS Foundation Trust. Reference: Panni RZ, Herndon JM, Zuo C, et al. Agonism of CD11b reprograms innate immunity to sensitize pancreatic cancer to immunotherapies. Sci Transl Med 2019 Jul 3;11(499).